Imaging cellular trafficking processes in real time using lysosome targeted up-conversion nanoparticles. Issue 94 (13th November 2017) - Pramanik, Sumit Kumar; Sreedharan, Sreejesh; Singh, Harwinder; Green, Nicola H.; Smythe, Carl; Thomas, Jim. A.; Das, Amitava
Abstract : Peptide conjugated upconverting nanoparticles for specific imaging of lysosome Abstract : β-NaYF4 :Yb, Gd up-conversion nanoparticles, UCNPs, surface functionalized with suitable targetting peptides function as nontoxic lysosome-specific imaging probes.